2016
DOI: 10.1161/circheartfailure.116.003129
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Loss of Kindlin-2 Leads to Progressive Heart Failure

Abstract: Background The striated muscle costamere, a multi-protein complex at the boundary between the sarcomere and the sarcolemma, plays an integral role in maintaining striated muscle structure and function. Multiple costamere-associated proteins, such as integrins and integrin-interacting proteins, have been identified and shown to play an increasingly important role in the pathogenesis of human cardiomyopathy. Kindlin-2 is an adaptor protein that binds to the integrin β cytoplasmic tail to promote integrin activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
(106 reference statements)
1
24
0
Order By: Relevance
“…Male chimeras were bred with female C57BL/6J mice to generate germline-transmitted BAG3 E455K mice Animal procedures, echocardiography, and hemodynamics. Echocardiography was performed as previously described (60,61). Briefly, mice were anesthetized with 1% isoflurane and underwent echocardiography using a FUJIFILM VisualSonics SonoSite Vevo 2100 ultrasound system blots analysis with antibodies against 14 proteins that had been found to be upregulated in the insoluble fraction of BAG3-CKO mouse hearts.…”
Section: Methodsmentioning
confidence: 99%
“…Male chimeras were bred with female C57BL/6J mice to generate germline-transmitted BAG3 E455K mice Animal procedures, echocardiography, and hemodynamics. Echocardiography was performed as previously described (60,61). Briefly, mice were anesthetized with 1% isoflurane and underwent echocardiography using a FUJIFILM VisualSonics SonoSite Vevo 2100 ultrasound system blots analysis with antibodies against 14 proteins that had been found to be upregulated in the insoluble fraction of BAG3-CKO mouse hearts.…”
Section: Methodsmentioning
confidence: 99%
“…16). Cardiac-specific knockout of kindlin-2 results in embryonic lethality, however postnatal cardiac-specific deletion led to fibrosis and heart failure indicating kindlin-2 is essential for integrin function (770). …”
Section: The Costamere: Protects Against Mechanical Stress and Is Anmentioning
confidence: 99%
“…Kindlin-2 not only modulates inside-out signaling by interacting with integrin β chains [20], but also contributes to outside-in signaling by binding to integrin-linked kinase [21]. More recently, it has been shown that Kindlin-2 can regulate integrin β 1 protein expression in adult cardiomyocytes [22]. Kindlin-2 is also involved in regulating cancer cell invasions with varying functions in different cancer types [23].…”
Section: Discussionmentioning
confidence: 99%